2013
DOI: 10.3762/bjoc.9.224
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial activity of monocyclic 3-carboxamide tetramic acids

Abstract: SummaryA chemical library of carboxamide-substituted tetramates designed by analogy with antibacterial natural products, a method for their rapid construction, and the evaluation of their antibacterial activity is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…This assignment was confirmed from a 1 H– 13 C NOE experiment of compound 11a in C 6 D 6 (Supporting Information). In contrast, carboxamide‐ and alkoxy‐carbonyl tetramic acids exist as the endo ‐enol form, reflecting their differing capacity for stabilising resonance …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This assignment was confirmed from a 1 H– 13 C NOE experiment of compound 11a in C 6 D 6 (Supporting Information). In contrast, carboxamide‐ and alkoxy‐carbonyl tetramic acids exist as the endo ‐enol form, reflecting their differing capacity for stabilising resonance …”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, a fully chemoselective Grignard displacement of Weinreb amides 7a-c has enabled the preparation of tetramic acids substituted with a range of side chain acyl groups; this alternative strategy to the classical acylation approach [7,12] offers a solution to the recently highlighted difficulty of the introduction of unsaturated side chains in such systems, [24] and neatly complements the work of Schobert which has demonstrated the suitability of Lacey-Dieckman cyclisation in highly sensitive substrates. [25] Some of these analogues had potent and selective activity against Gram-positive bacteria, and one is a first-in-class proteasome inhibitor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several compounds containing pyran rings have been tested for their microbiocide properties (Rajan et al, 2017) and derivatives of 2H-pyran (thiourea and benzene sulfonylurea) possess antimicrobial activities (Faidallah et al, 2011). Carboxamides are not only being used as site-specific fungicides (Jangir et al, 2018) but have also been shown to possess antibacterial properties (Jeong and Moloney, 2013). Hence, it suggests that at least part of the inhibitory effects caused by these bioinoculants could be attributed to antibiosis triggered by the release of bioactive compounds during root colonization.…”
Section: Discussionmentioning
confidence: 99%
“…24 Also, the carboxamide derivatives of tetramic acids based on antibacterial natural products have been shown to have bioactivity against various Gram-positive bacteria and also the Gram-negative organism H. influenzae . 25 Finally, using molecular hybridization, a series of carboxamide derivatives were synthesized and shown to be active against Mycobacterium tuberculosis (MTB). 26 These results, along with the activity of BT_03F04 observed against Gram-positive pathogens, indicate that further evaluation of a carboxamide-based lead series based on this compound may be advantageous.…”
Section: Discussionmentioning
confidence: 99%